2020
DOI: 10.1371/journal.pone.0241686
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of classification and forecasting methods on time series gene expression data

Abstract: Time series gene expression data is widely used to study different dynamic biological processes. Although gene expression datasets share many of the characteristics of time series data from other domains, most of the analyses in this field do not fully leverage the time-ordered nature of the data and focus on clustering the genes based on their expression values. Other domains, such as financial stock and weather prediction, utilize time series data for forecasting purposes. Moreover, many studies have been co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Tripto et al . [ 114 ] evaluated Holt–Winters, ARIMA, LSTM, Artificial Neural Network (ANN) and GluonTS feedforward neural networks for forecasting time series in five sets of temporal gene expression profile data of different sizes, and found that ARIMA and ANN worked better.…”
Section: Proposed Research Directions and Methodsmentioning
confidence: 99%
“…Tripto et al . [ 114 ] evaluated Holt–Winters, ARIMA, LSTM, Artificial Neural Network (ANN) and GluonTS feedforward neural networks for forecasting time series in five sets of temporal gene expression profile data of different sizes, and found that ARIMA and ANN worked better.…”
Section: Proposed Research Directions and Methodsmentioning
confidence: 99%
“…Machine algorithms and in specific, neural networks, are emerging as state-of-the-art approaches in time series forecasting and classification of complex systems, including gene expression dynamics. 166 Once again, none have been applied in cancer research due to the lack of cancer time series datasets. In principle, the neural networks discussed below can and should be utilized to study attractor dynamics from time series cancer datasets.…”
Section: Causality Inference Via Machine Intelligencementioning
confidence: 99%
“…While autoregression models are better suited for short-term time series forecasting in low-dimensional systems, deep learning algorithms are the state-of-the-art approaches for time series gene expression forecasting in higher-dimensional systems. 166 Furthermore, neural network algorithms used in turbulence forecasting may be of great interest in the application to cancer dynamics prediction. If the AI can predict causal patterns, such as strange attractors in turbulent flows, then it should (in principle) within cancer datasets as well.…”
Section: Causality Inference Via Machine Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…To validate our proposed method, we used the E. coli dataset with the same topological features used in S. Cerevisiae and seven different time series of the gene expression as biological features. The time series of the gene expression is the expression of the gene at different time points [46]. Many existing methods used this gene expression data for different purposes of classification [11,28,34].…”
Section: Introductionmentioning
confidence: 99%